Immune Status Against Hepatitis B Infection in Children with Thalassemia Major in Pakistan: A Single-Centre Study - Fakih, Misbah; Basheer, Faisal; Khan, Qamar uz Zaman; Hashmi, Fasih; Asad, Hafsa (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To assess the immunogenicity of the Hepatitis B Vaccine in children with thalassemia. Study Design: Prospective longitudinal study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan from Aug 2018 to Jan 2019. Methodology: After ethical approval and informed consent, 150 diagnosed patients with thalassemia were selected from the Thalassemia centre at Pak Emirates Military Hospital Rawalpindi. The patients’ transfusion, vaccination history and clinical data were obtained. The patient’s sera were tested for Anti-Hepatitis B surface antibodies (anti-HBs) by ELISA. The patients who showed seroprotection (anti-HBs titer>10 IU/L) were taken as a case group. Results: Out of 150 patients, only 22% (33 patients) showed seroprotection (anti-Hbs titer>10 IU/L). Children younger than four years had significantly positive anti-HBs (p-value=0.067) at a 5% significance level. Time since the last vaccination was also a significant factor, with the 3.76±3.072 years range exhibiting better protection (p=0.002). Conclusion: Protective Anti-HBs titer was reduced after the age of 4 years in our patients, so we recommend screening patients with thalassemia after four years to assess the need for a booster dose.